2017
DOI: 10.4103/0970-1591.203412
|View full text |Cite
|
Sign up to set email alerts
|

Bladder cancer: Micro RNAs as biomolecules for prognostication and surveillance

Abstract: Introduction:Bladder cancer (BC) has varied clinical behavior in terms of recurrence and progression. Current pathological characteristics are insufficient to prognosticate the outcome of a given treatment. Cellular metabolic regulatory molecules, such as micro RNA (miRNA), could be a potential biomarker to prognosticate the treatment outcomes.Materials and Methods:PubMed and Google Scholar databases were searched for publications from 1990 to 2016, related to miRNA biogenesis, its function, and role in the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…However, in most of these studies, only the deregulation of miR is considered, without any clue about the miR role in BC etiology. A recent meta-analysis performed by searching the PubMed and Google Scholar databases for publications ranging between 1990 and 2016 allowed identifying at least 35 miR specifically associated with different pathways of cellular dedifferentiation, proliferation, and progression of BC as well as of other cancers [ 184 ]. In this review, we have focused only on miR with an established role in urothelium neoplastic transformation by means of at least one identified target gene ( Table 3 ) and have discussed only a few of them as prominent examples.…”
Section: Small Non-coding Rnamentioning
confidence: 99%
See 1 more Smart Citation
“…However, in most of these studies, only the deregulation of miR is considered, without any clue about the miR role in BC etiology. A recent meta-analysis performed by searching the PubMed and Google Scholar databases for publications ranging between 1990 and 2016 allowed identifying at least 35 miR specifically associated with different pathways of cellular dedifferentiation, proliferation, and progression of BC as well as of other cancers [ 184 ]. In this review, we have focused only on miR with an established role in urothelium neoplastic transformation by means of at least one identified target gene ( Table 3 ) and have discussed only a few of them as prominent examples.…”
Section: Small Non-coding Rnamentioning
confidence: 99%
“…Therefore, miR-205 is possibly involved in many biochemical processes, including carcinogenesis. miR-205 may act as a diagnostic and prognostic BC marker, since it has been discovered that a mucosa with a normal appearance may have molecular changes (that precede phenotypic changes) in the form of varied expression of this molecule, besides other miR, such as miR-129 and miR-200a [ 184 ]. miR-21 targets many genes that can be involved in the formation and development of cancer, including TP53 [ 207 ], PTEN, TIMP3 (tissue inhibitor of metalloproteinase 3) (both inhibitors of the matrix metalloproteinases), BCL-2 (regulator of apoptosis) [ 208 ], and many others; its overexpression is linked to loss of function of TP53, which is most commonly observed in high-grade MIBC [ 209 ].…”
Section: Small Non-coding Rnamentioning
confidence: 99%
“…Most noteworthy for our purpose of specificity as an oncocytoma marker, miR-205 is downregulated in prostate cancers [ 54 ]. Furthermore, most publications (except [ 55 , 56 ]) also report a downregulation in bladder cancer, including a review of 108 relevant publications [ 57 , 58 ]. In addition, a study focusing on miR levels in biofluids (serum, urine) has found that miR-205 was so low that it can no longer be considered a useful biomarker [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, abnormal expression of miRNA in BC is thought to benefit for the development of BC 10,11. Studies find that miRNA can be used as a marker for diagnosing BC and prognosis 1214. MicroRNA-124 is considered to be brain-enriched and is an extremely conserved gene 15.…”
Section: Introductionmentioning
confidence: 99%